Yogurt drink fortified with menaquinone-7 improves vitamin K status in a healthy population - Knapen, Marjo H. J. (J Nutr Sci, 2015)
Population-based studies have shown an inverse association between dietary menaquinones (MK-n, vitamin K(2)) intake, coronary calcification and CHD risk, suggesting a potential role of vitamin K in vascular health. To date, the effects of increased menaquinone intake on (markers of) vascular health have been investigated using predominantly food supplements. Dairy products contain many essential nutrients and can serve as a good matrix for food fortification in order to support health. We were therefore interested to study the effects of a menaquinone-fortified yogurt drink (menaquinone as menaquinone-7 (MK-7); 28 µg MK-7/yogurt drink) on vitamin K status and markers of vascular health. The yogurt drink was also fortified with n-3 PUFA, vitamin D, vitamin C, Ca and Mg to support vascular and/or general health. Healthy men (n 32) and postmenopausal women (n 28) with a mean age of 56 (sd 5) years received either basic or fortified yogurt drink twice per d for 12 weeks. MK-7 was efficiently absorbed from the fortified yogurt drink. Levels of circulating MK-7 were significantly increased from 0·28 to 1·94 ng/ml. In accordance, intake of the fortified yogurt drink improved vitamin K status, as measured by significant decreases in uncarboxylated osteocalcin and desphospho-uncarboxylated matrix Gla-protein. No effects were, however, seen on markers of inflammation, endothelial dysfunction and lipid metabolism. In summary, consumption of a yogurt drink fortified with low doses of among others MK-7 for 3 months significantly improved vitamin K status in a healthy population.